Tackling graduate unemployment in North Africa through employment subsidies: A look at the SIVP programme in Tunisia - Stijn Broecke (IZA Journal of Labor Policy, 2013)
This paper takes a closer look at Tunisia's SIVP: an employment subsidy aimed at university graduates and, until recently, the country's largest active labour market policy. Using a tracer survey of the 2004 graduating cohort, OLS and matching techniques are applied to estimate the relationship between programme participation and the labour market outcomes of participants. Graduates who benefited from the programme appear less likely to be unemployed and considerably more likely to have found a job in the private sector - but this may partly reflect selection into the programme, which is not random.
Keywords: J08; J20; 330; Graduate unemployment; Employment subsidy; MENA